The relationship between fibular head height and lower limb alignment deviation and severity after TKA for varus deformity knee osteoarthritis - Xun Qin; Hengzhi Liu; Yinghao Liu; Aixin Hu (PLoS ONE, 2025)
Purpose To investigate the correlation between fibular head height and the deviation and severity of lower limb alignment after TKA in patients with varus deformity and knee osteoarthritis. Methods Based on the varus angle (γ = 10°), the sample was divided into two groups: < 10° and ≥10°, The differences in fibular head height between the two groups of patients were analyzed using an independent samples t-test; The Mann-Whitney test was used to analyze the differences in fibular head height between genders. An unordered multinomial logistic regression analysis was conducted to evaluate the effects of age, gender, height, weight, body mass index, and fibular head height on postoperative lower limb alignment; Pearson correlation analysis was used to assess the correlation between fibular head height and varus angle, preoperative HKA angle, and postoperative HKA angle; A Multiple linear regression was performed to evaluate the effects of gender, age, height, weight, body mass index, fibular head height, preoperative HKA angle, and varus angle on the postoperative HKA angle. Results The sample was divided into two groups based on the varus angle: ≥ 10° and <10°. The fibular head height was 8.1825 ± 2.72505 mm in one group and 9.2234 ± 2.68225 mm in the other group (p = 0.028 < 0.05), which was statistically significant; The median fibular head height in females was 8.050 mm, compared to 10.645 mm in males (p < 0.05), which was statistically significant. In the unordered multinomial logistic regression, with postoperative lower limb alignment (varus, valgus, neutral) as the dependent variable, In the unordered multinomial logistic regression with postoperative lower limb alignment as the dependent variable, Height, weight, and body mass index are influencing factors for postoperative lower limb alignment in patients with varus deformity knee osteoarthritis, affecting both varus and valgus alignment, while fibular head height is a significant factor for postoperative varus alignment. In the Pearson correlation analysis, fibular head height was positively correlated with postoperative HKA angle (r = 0.212, p < 0.05). In the multiple linear regression with postoperative HKA angle as the dependent variable, fibular head height and preoperative HKA angle were identified as significant factors influencing the postoperative HKA angle (p < 0.05). Conclusions This study found that in patients with varus deformity knee osteoarthritis, a greater degree of varus was associated with a lower fibular head height. Additionally, the fibular head in female patients was positioned closer to the lateral tibial plateau compared to male patients. In varus deformity knee osteoarthritis, fibular head height is a risk factor for postoperative lower limb varus alignment following total knee arthroplasty (TKA). Patients with a higher-positioned fibular head (lower fibular head height) are more likely to develop postoperative varus malalignment after TKA. Therefore, routine measurement of fibular head height is warranted in clinical practice for patients with varus deformity knee osteoarthritis.